Association between Life’s Essential 8 and psoriasis in US adults: a cross-sectional study - Zhang, Junjie; Ren, Ci; Qin, Zihan; Zhu, Ling; Jin, Zhoufeng; Yan, Yuanyuan; Pan, Xinghe; Luan, Lan (Frontiers in Medicine, 2024)
Background Psoriasis is closely associated with cardiovascular disease (CVD). However, the current evidence on the correlation between Life’s Essential 8 and Psoriasis is insufficient. Our aim was to investigate the relationship between Life’s Essential 8 (LE8), a measure of cardiovascular health (CVH), and psoriasis. Objective This study aimed to clarify the impact of Life’s Essential 8 on Psoriasis and explore its implications. Methods This population-based cross-sectional study included 9,876 US adults aged 20 to 59 years from the National Health and Nutrition Examination Survey (NHANES) 2003–2006 and 2009–2014 cycles. The LE8 score comprises 8 metrics and was categorized into low, moderate, and high CVH. Logistic regression and restricted cubic splines (RCS) were used to assess the association between LE8 score and psoriasis. Results Among the 9,876 participants, those with moderate and high CVH had higher risks of psoriasis compared to low CVH. Additionally, every 10-point increase in the LE8 score was associated with a 10% reduced risk of psoriasis. Interaction was observed between gender, age, education level, race/ethnicity, marital status, and PIR. Conclusion LE8 and its subscale scores were strongly negatively related to the risk of psoriasis. Encouraging optimal CVH levels may be advantageous in reducing the incidence of psoriasis.